SPE Latin American and Caribbean Petroleum Engineering Conference 2010
DOI: 10.2118/139200-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dina Cretáceos Field Chemical EOR: From Screening to Pilot Design

Abstract: Dina Cretaceous Field is located in the Upper Magdalena Valley (UMV) Basin, Colombia. Producing reservoir consist in a marine-transitional depositional environment with good sand continuity and thickness. Ecopetrol S.A operates the field. The field was discovered in 1969. Primary production peaked at 6,500 BOPD. Peripheral water injection started in 1985 reaching a maximum oil production rate of approximately 10,000 BOPD. Current recovery factor is estimated in 32% of the OOIP with water cuts of 96%. Water inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…20. Lantz (2010), Sandoval et al (2010), Mack and Lantz (2013), and the ICP methodology presented by and Maya et al (2014) showed in their basic decision making scheme for chemical flooding that in case of mature water floods with high recovery factors, there is low probability of success for conformance technologies and there is a need for a combination of sweep improvement and residual oil saturation reduction technologies. They pointed out that in these cases; the surfactant-based technologies (ASP/ SP) are the candidates.…”
Section: Flood Maturitymentioning
confidence: 99%
“…20. Lantz (2010), Sandoval et al (2010), Mack and Lantz (2013), and the ICP methodology presented by and Maya et al (2014) showed in their basic decision making scheme for chemical flooding that in case of mature water floods with high recovery factors, there is low probability of success for conformance technologies and there is a need for a combination of sweep improvement and residual oil saturation reduction technologies. They pointed out that in these cases; the surfactant-based technologies (ASP/ SP) are the candidates.…”
Section: Flood Maturitymentioning
confidence: 99%
“…In more than 40 historic cases, operators have reported incremental recovery factors of up to 10% of the Original Oil In Place (OOIP) (Demin, Yingjie, Yan & Xuping, 2002;Chang et al, 2004;Norman, De Lucía & Turner, 2006;Sandoval et al, 2010;Castro et al, 2013). CDG technology is used to improve volumetric -neity of the reservoir and the adverse mobility ratio in have been implemented in Colombia, along with 6 pilots that are currently underway.…”
Section: Theoretical Framework and State Of The Artmentioning
confidence: 99%
“…Three methodologies have been presented in the literature for pilot area selection. The first category presents some qualitative insights regarding the pilot area, such as the necessity of using predictive reservoir simulation models [4,[7][8][9][10]. These studies do not provide any quantitative methods to select a pilot area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, having remaining oil saturation in the range of 0.2-0.5 could lead to an appropriate pilot area [11]. According to other studies [7,8], high remaining oil saturation has been applied to locate pilot areas. In addition, a lower ratio of vertical to horizontal permeability and higher lateral permeability continuity have also been a basis for pilot area selection [15,16].…”
Section: Introductionmentioning
confidence: 99%